How Do College Students Solve Logarithm Questions? - Aziz, Tian Abdul; Pramudiani, Puri; Purnomo, Yoppy Wahyu (International Journal on Emerging Mathematics Education, 2017)
The purpose of the study was to investigate college students' work with logarithm questions. Qualitative descriptive research is chosen to reach the research goal. The participants of the study were fourteen Indonesian students who were enrolled at different universities in Ankara, Turkey. They worked to solve ten logarithm questions which were classified according to the contents. After analysing their written responses, interviews were conducted to obtain further explanation about their strategies and common mistakes. The study found that participants' works in dealing with logarithm questions comprised of (a) processing base, (b) holding the rule, (c) separating, (d) jumping, and (e) conditioning. Therewith, several participants made common mistake because of misconception about logarithm, arithmetical problems, and misuse of algebra concept. Implication of the finding of the study for teaching and learning logarithm were presented.